Quantitative surface characterization of silicon spheres by combined XRF and XPS analysis for the determination of the Avogadro constant. (4th August 2017) - Müller, Matthias; Beckhoff, Burkhard; Beyer, Edyta; Darlatt, Erik; Fliegauf, Rolf; Ulm, Gerhard; Kolbe, Michael
Abstract: For the quantitative surface characterization of a monocrystalline silicon sphere, PTB has constructed and put into operation an analytical instrument, which combines x-ray fluorescence and x-ray photoelectron spectroscopy techniques. The main objective of this novel instrument is the characterization of the oxide layer and unintentional contaminations, e.g. from hydrocarbons. It is equipped with a ball manipulator allowing measurements at each point on the surface of ball-shaped samples with a diameter of about 93.7 mm. Monocrystalline silicon spheres with this diameter allow a realization of the SI base unit of mass.